The Deradicalization Paradox: When Former Terrorists Become Perpetrators of Economic Crimes - Sofyan, Muhammad; Priyanto, Sapto (Security Intelligence Terrorism Journal (SITJ), 2025)
This study investigates the paradoxical emergence of "zero terrorist attacks" in Indonesia from 2023 to mid-2024, alongside the growing involvement of former terrorism convicts (ex-napiter) in illicit economic activities. While Indonesia’s counter-terrorism strategy has been hailed as successful in preventing violent extremism, reports indicate that numerous ex-napiter are actively engaged in illegal enterprises such as subsidized fuel smuggling, unauthorized mining, and unlicensed vehicle leasing. Utilizing a qualitative descriptive approach and drawing upon Abraham Maslow’s hierarchy of needs theory, this research explores the motivations driving these individuals from ideological militancy to economic criminality. Data were collected through document analysis and field interviews conducted in April 2025 across multiple regions. The findings reveal that unmet economic and psychosocial needs, particularly related to esteem and security, have led many former convicts to seek recognition and income through informal and illegal means. These developments raise critical concerns about the effectiveness of reintegration programs that prioritize ideological transformation over sustainable economic support. The article concludes by recommending an integrated reintegration model grounded in the fulfillment of human needs, community engagement, and localized governance reform. This framework aims to reduce recidivism, prevent radical resurgence, and ensure a lasting peace beyond the absence of physical violence.